(untitled) (Applied Biological Research, 2015)
The present study was aimed to assess the effect of black cumin (Nigella sativa) oil on serum lipid profile and β-hydroxy, β-methylglutaryl coenzyme-A reductase (HMG CoA reductase) gene expression in adult layer birds. Thirty six weeks old White Leg Horn (WLH) layer birds were randomly divided into five groups consisting of 6 birds each. Their diets were supplemented with 0 (control), 1.0, 2.0, 3.0 and 4.0 g black cumin oil kg-1 feed, respectively. Blood samples were collected on day 0, 14, 28, 42 and 56 and study further continued for one more month without supplementing the diet with herbal preparations in order to observe the withdrawal effect. Gene expression studies of HMG CoA reductase were carried out in the liver tissue of the birds by real time quantitative PCR analysis on day 56. Serum total lipids, cholesterol, tri glycerides, HDL, LDL and VLDL-cholesterol varied highly significantly (p<0.01) between treatments and intervals. Maximum reduction in HMG CoA reductase gene expressions was noticed in group fed diet supplemented with 4 g cumin oil kg-1. The reduction pattern in gene expression and serum lipid profile in treatment groups fed diets supplemented with black cumin oil were in the order of 4> 3> 2> 1> 0 g cumin oil kg-1 feed. The study revealed that the supplementation of black cumin oil @ 4 g kg-1 feed is most effective in reducing serum lipid profile and HMG CoA reductase gene expression after 56 days. These effects gradually reduced with time after the withdrawal of oil.